2018
DOI: 10.1186/s12889-018-5749-2
|View full text |Cite
|
Sign up to set email alerts
|

Precarious transition: a mortality study of South African ex-miners

Abstract: BackgroundDespite their burden of a triple epidemic of silicosis, tuberculosis and HIV infection, little is known about the mortality experience of miners from the South African mining industry once they leave employment. Such information is important because of the size and dispersion of this population across a number of countries and the progressive nature of these diseases.MethodsThis study included 306,297 South African miners who left the industry during 2001–2013. The study aimed to calculate crude and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…It was and still is thought that mining is not a woman's job [17], although by 2017 at least 12% of miners were female. In a study by Bloch et al (2018) using mining recruiter data, ex-miner mortality from 2001-2013 was investigated, where 5.1% of ex-miners were female [16]. In our study of registered deaths from 2013 to 2015, a similar proportion (5.7%) of miners were female.…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…It was and still is thought that mining is not a woman's job [17], although by 2017 at least 12% of miners were female. In a study by Bloch et al (2018) using mining recruiter data, ex-miner mortality from 2001-2013 was investigated, where 5.1% of ex-miners were female [16]. In our study of registered deaths from 2013 to 2015, a similar proportion (5.7%) of miners were female.…”
Section: Discussionmentioning
confidence: 51%
“…In our study of registered deaths from 2013 to 2015, a similar proportion (5.7%) of miners were female. Bloch et al (2018) found no excess mortality in women ex-miners, while an average of 20% excess mortality was found in men. Their finding of a lack of excess mortality in women miners was limited by the fact that the mortality rate in ex-miners decreased over the years in the study and women were only employed in the later years.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations